Studying developers for fun and profit - DeLIne, Robert (Program Comprehension (ICPC), 2012 IEEE 20th International Conference on, 2012)
My group at Microsoft Research creates software development tools through user-centered design. This method creates a virtuous cycle: we study developers and their teams, which in turn inspires the tools we design, which we then evaluate with those developers and teams, seeking to improve the nature of their work. In this talk, we'll discuss some of the biggest problem areas we have observed, including information seeking, multitasking and disorientation, and look at some of the prototypes we have built in response. Code Canvas provides a zoomable map of a software project, allowing the programmer to zoom out to see structure and visualizations and zoom in to edit code. Debugger Canvas (a joint project with Brown University) provides a spatial representation of a programmer’s task, like a debugging session, as it unfolds. Finally, Code Space uses a combination of touch screens, Kinects and mobile devices to allow fluid sharing of digital objects at development team meetings.